2009
DOI: 10.1590/s1984-82502009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-project of implantation of pharmaceutical care close to the program of bipolar mood disorder of the Hospital of Clinics of Porto Alegre

Abstract: The Bipolar Mood Disorder is characterized by the alternation of depressive crises with episodes of mania or euphoria, having these patients 15 to 35 times more chances of suicide, as compared with people without this disorder. The pharmacotherapy is fundamental for this disease, aiming to decrease the frequency of episodes and disease severity. In these patients, the polypharmacy has recently increased and one of the main difficulties is the adherence to treatment. The objective of this study was to contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Studies that have employed the Dáder Method have shown its effectiveness in several diseases, but there are no data on patients being treated for depression. [20][21][22] Due to the worldwide advancement of PC and the need to assess its effectiveness in female patients with depression, the present clinical trial sought to employ and assess the Dáder Method of PF. Our hypothesis states that the Dáder Method is effective and results in the clinical improvement of depressive and anxious symptoms.…”
Section: Intervention Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have employed the Dáder Method have shown its effectiveness in several diseases, but there are no data on patients being treated for depression. [20][21][22] Due to the worldwide advancement of PC and the need to assess its effectiveness in female patients with depression, the present clinical trial sought to employ and assess the Dáder Method of PF. Our hypothesis states that the Dáder Method is effective and results in the clinical improvement of depressive and anxious symptoms.…”
Section: Intervention Designmentioning
confidence: 99%
“…Thus, the pharmacist would be the suitable professional to monitor patients through pharmaceutical care, working with the doctor. • It has been observed that the use of pharmacists in the mental health system is in its early stages, and few studies have been developed outside the United States with the objective of demonstrating the importance of the pharmacist on the mental health team (Razali et al, 1995;Shaw, 2000;Prats and Cebrián, 2002;Castelló, 2002;Ceresér et al, 2009). There are few randomized controlled trials, 3 of them were developed in the United States Capoccia et al, 2004;Adler et al, 2004) and 2 in the Netherlands (Brook et al, 2003, Brook et al, 2005, which do not specify the method used in pharmaceutical care.…”
mentioning
confidence: 99%
See 1 more Smart Citation